Designing a Learning Media of English for Specific Purpose based on Interactive Multimedia (Macromedia flash 0.8) for Agro-Industry Students - Selfa Idriani; Shally Amna (JURNAL ARBITRER, 2019)
The research objective is to design a learning media of ESP using Macromedia Flash 0.8, which can contribute comprehension in learning ESP and presenting the validation of the media. The Procedure development referred to development research that uses model 4D by Borg and Gall. The development consists of 4 steps. They are defined, design, develop, and disseminate. The data ware collected through validation by media experts, material experts, and practitioners using questionnaires and interviews. Then, the data are presented by using tables. The result of validation by media expert on the media developed obtained a total score of 87.5 % belonging to valid with no revision, the result of validation by material expert obtained a total score of 90 %belonging to valid with revision and validation by practitioners obtained a total score of 8.589 % belonging to valid with no revision. The result showed that the use of interactive multimedia by using a Macromedia flash 0.8 is recommended to be implemented because the students can relatively access to media which is operated with android. The result of this research will be used as a matrix for the next research, which is the development of ESP Module based on interactive multimedia.